The role of cultural familiarity toward reading comprehension and motivation among Iranian students - Ghaderpour, Mahsa (2013)
Familiarity with cultural perspective of reading text is one of the significant issues in language learning classrooms. The lack of sufficient knowledge of learners regarding the target culture of language costs them some difficulties to comprehend the target reading text. For this reason, learner?s motivation would be decreased to acquire the new language. This study has attempted to discover the importance of cultural background knowledge toward reading comprehension and also participants motivation. Hence, quantitative method was conducted and 30 Iranian students who joined IEC classes in University Technology of Malaysia participated in this study. For the purpose of identify the role of background study, the original and nativised texts were given to participants. They also expressed their motivation toward cultural perspective through a 5-point Likert Scale survey questionnaire. The results indicated that cultural background knowledge enhances the comprehension of reading text as well as motivation toward learning the new language. The pedagogical implications of the findings imply the significant role of cultural background knowledge in the English language learning classroom. Hence, the integration of cultural perspective with language instruction in the foreign language learning classroom was recommended in this study.